Brand Equity on Banking Sector - Prajapat, Ms. Swati; Ojha, Dr. Nupur (The journal of contemporary issues in business and government, 2022)
A measure of the benefit of having a recognizable and quite well brand is brand equity, or the maximum power a strong brand has in the customer's mind. Brand equity is built by providing great customer experiences that encourage people to choose them over rivals that provide identical items. Banking sector, now-a-days, are having cut throat competition in almost all the scheduled commercial banks of India. This shows that banks should maintain its brand equity to compete with other banks. According to Aaker, perceived quality, association, loyalty and brand awareness are the variables to measure Brand Equity. The study took the help of customers of the PSBs and PVBs of India to measure all the variables of brand equity.